Influence of drilling parameters on thrust force and burr on fiber metal laminate (Al 2024-T3/glass fiber reinforced epoxy) - Bonhin, Eduardo Pires [UNESP]; David-Müzel, Sarah [UNESP]; Guidi, Erick Siqueira [UNESP]; Botelho, Edson Cocchieri [UNESP]; Ribeiro, Marcos Valério [UNESP] (Elsevier, 2020)
In the present work a fiber metal laminate (FML) of three aluminum sheets interspersed with eight layers of glass fiber reinforced epoxy was used. The processes were carried out using 4000 and 8000 rpm and a 0.05; 0.10 and 0.20 feed in mm/rev with a coated carbide drills (TiAlN) with Ø4.8 mm. With the found results, it could be stated that the thrust force was affected significantly by the feed with 99.75% of contribution, the burrs thickness was influenced by spindle speed and feed (27.59% and 63.14% respectively), and burrs height by feed and interaction between factors (21.33% and 75.76%).
Keywords: Composite; Drilling; Monitoring